Variations of the Mycobacterium abscessus F-ATP synthase subunit a-c interface alter binding and potency of the anti-TB drug bedaquiline - Krah, Alexander (2023)
The anti-tuberculosis therapeutic bedaquiline (BDQ) is used against Mycobacterium abscessus. In M. abscessus BDQ is only bacteriostatic and less potent compared to M.tuberculosis or M. smegmatis. Here we demonstrate its reduced ATP synthesis inhibition against M. abscessus inside-out vesicles, including the F1FO-ATP synthase. Molecular dynamics simulations and binding free energy calculations highlight the differences in drug- binding of the M. abscessus and M. smegmatis FO-domain at the lagging site, where the drug deploys its mechanistic action, inhibiting ATP synthesis. These data pave the way for improved anti-M. abscessus BDQ analogs.